A stream sediment geochemical orientation study in Derince (Keban-Elazi?) vicinity - Bölücek, Cemal (My University, 2002)
The study area including massive sulphide and vein type mineralizations is in a non-contaminated environment. It has a semi-arid climate and rough topography. Suitable sediment fraction, dissolution method and metal dispersion patterns were determined suitable for such an area by stream sediment orientation survey. The physico-chemical features of the area indicates that the metalic contents of the stream sediments originate from physical rather than chemical processes. -80+200 mesh fractionseems to be the most suitable fraction and this fraction is chosen for the analyses. In order to determine the most effective solution method, several methods were experimented and aqua regia digestion was considered as the most effective method due to high values obtained, readily dissolution of the samples, multi element determination from the same solution and rapid sample prepration. In the southern part of Derince, where volcano-sedimantary and volcanic rocks crop out, and Cu, Zn, Cd and (Co) anomalies exist. Low grade Pb anomalies were determined in the vicinity of Çayecorik Stream, where tonalitic rocks are observed.
Derince (Keban-Elazi?) çevresinde dere sedimenti jeokimyasal yönlendirme çalişmasi
Keywords: Aqua regia; Derince (Keban-Elazi?); Stream sediment